Land, law, and indigeneity in Mexico - Gabriela Torres-Mazuera (Oñati Socio-Legal Series)
Despite the 2024 constitutional reform that acknowledges legal standing to indigenous communities, in Mexico there is still no legal provision to protect and recognize indigenous territories at the national level. Conversely, since the agrarian legal reforms of the 1990s, the commodification of communal landholdings (ejido and agrarian communities) considered a safeguard for “indigenous lands” have escalated. How do indigenous communities, landed property, and territory intersect in contemporary Mexico? Furthermore, which legal frameworks interact in the resolution of ongoing agrarian conflicts involving indigenous communities? This article addresses these questions by conceptualizing agrarian and indigenous communities as intertwined and evolving sociopolitical institutions. It challenges a long-standing judiciary’s formalist approach, which, by conceiving these communities, primarily as transhistorical and self-contained subjects of rights, with apparently juxtaposed claims (i.e., the right to landed property versus the right to self-governance and territory) have precluded the peaceful and effective resolution of historical agrarian conflicts.